Examining Science Process Skills Tests: A Case of Turkey - Burçin Acar Şeşen; Okan Sıbıç (International Journal of Assessment Tools in Education)
One of the main goals of science education is to make students gain science process skills. Thus, it is significant to measure whether students gain those skills or not. For this purpose, various tests have been produced and used in various studies. This study aims to examine science process skills tests which have been used in the theses produced in the field of science education from the perspectives of the originality, question types used, and the science process skills measured in the tests, and the number of questions for each measured science process skill. Within the scope of this meta-synthesis study, 82 master’s theses and 34 doctoral dissertations from Turkey were analyzed. The findings indicate that science process skills were measured with multiple-choice tests, and only in smaller number of studies, original tests were developed for the corresponding study. It was also discovered that some science process skills were measured more frequently than others. As a result of the study, some suggestions were provided.